2017
DOI: 10.1186/s13018-017-0591-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the location of placement of meniscal sutures have a clinical effect in the all-inside repair of meniscocapsular tears?

Abstract: BackgroundMeniscocapsular separation (MCS) is a lesion of the area which is attached from the peripheral section of the meniscus to the capsule and is seen less often than other meniscus injuries. The aim of this study was to investigate which of the different side applications of all-inside MCS repair of the meniscus was better in respect of clinical and functional results.MethodsIn this retrospective study, 53 patients with MCS pattern in their knee joints were treated with arthroscopic meniscus repair made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…Placing the patient's knee into the figure-of-4 position resulted in varus stress, reducing this inward displacement. Our patient presentation was consistent with that previously reported in the literature for isolated MCS: teenage female athlete with joint line tenderness limited to the area of separation, with or without McMurray or mechanical symptoms, and pain that typically only occurs with sporting activities but not with activities of daily living (Table 1) [5][6][7].…”
Section: Discussionsupporting
confidence: 88%
“…Placing the patient's knee into the figure-of-4 position resulted in varus stress, reducing this inward displacement. Our patient presentation was consistent with that previously reported in the literature for isolated MCS: teenage female athlete with joint line tenderness limited to the area of separation, with or without McMurray or mechanical symptoms, and pain that typically only occurs with sporting activities but not with activities of daily living (Table 1) [5][6][7].…”
Section: Discussionsupporting
confidence: 88%
“…Second, we did not investigate the consequences of suture shape in meniscus repair after surgery because the outcomes in this study were measured at time zero after surgery. Third, we conducted our biomechanical analysis only on the middle segment of the medial meniscus, and a recent study indicated that the location of sutures in the meniscus may affect their biomechanical features (Tiftikci and Serbest 2017 ). Finally, we did not investigate all-inside devices or sutures made of ultra-high-molecular-weight polyethylene (UHMWPE).…”
Section: Discussionmentioning
confidence: 99%
“…Quadriceps strength and ROM were evaluated and incorporated as part of the rehabilitation guidelines for a few of the included studies that implemented them into their return-to-play criteria. 14 , 15 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 The use of arthroscopic findings to help determine to what level an athlete could return-to-play was not used in the included studies. However, Willinger et al.…”
Section: Discussionmentioning
confidence: 99%